Features of corporate well-being - Burlakova, Iryna; Sheviakov, Oleksiy; Kondes, Tetiana; Кондес, Тетяна Василівна; Кондес, Тетяна (Scientific Center of Innovative Researches OÜ, 2020)
The monograph is the result of multifaceted research on corporate management. In particular, the authors focused on the managerial, financial and psychological aspects of corporate governance, as they are the most vulnerable to the challenges and threats of the new reality. The key provisions of the study focus on the formulation of new scientific hypotheses, methods and tools for corporate management. The publication is intended for researchers, civil servants, university professors and students, practitioners, and a wide range of readers interested in corporate management issues
Keywords: corporation; corporate management